The role and activities of the Traveller mental health liaison nurse: Findings from a multi-stakeholder evaluation - Keogh, Brian; O'Sullivan, Karin; Downes, Carmel; Brady, Anne-Marie; Doyle, Louise; Higgins, Agnes (My University, 2021)
Irish Travellers are a minority ethnic group within the Irish state with a distinct culture and set of traditions. Travellers experience mental health inequalities, high rates of mental ill health, and structural and individual barriers to mental health supports. A Traveller Mental Health Liaison Nurse (TMHLN) was introduced in a healthcare region in Ireland to provide greater mental health-related support to Travellers. This paper presents a description of the TMHLN role following a multi-stakeholder evaluation. The research design was descriptive qualitative and the findings are reported using COREQ criteria. Thirty-four key stakeholders were interviewed individually or as part of focus groups. Thematic analysis generated two broad themes: the role context, and the specific activities of the role. Mental health nursing experience and understanding of local issues and services were key, as was use of language, building trusting relations, creating the metaphorical, and having the physical, space for working. Specific activities involved in-reach and outreach work, including one-to-one mental health support provision, delivery of education/training sessions to Travellers and service providers, (re)establishing links to specialist services, integrated and interagency working, and promoting cultural competency. The findings set out a role with a greater emphasis on the use of recovery technologies, having an emphasis on psychosocial interventions and self-care, and less focus on biomedical technologies, signs and symptoms, and clinical outcomes. This study contributes to knowledge on the role of a MHLN as this relates to working with marginalized minority groups.
PUBLISHED
Keywords: evaluation; liaison nursing; minority group; qualitative research; Traveller mental health